Fusarium praegraminearum sp. nov., a novel nivalenol mycotoxin-producing pathogen from New Zealand can induce head blight on wheat. (1st November 2016) - Gräfenhan, Tom; Johnston, Peter R.; Vaughan, Martha M.; McCormick, Susan P.; Proctor, Robert H.; Busman, Mark; Ward, Todd J.; O'Donnell, Kerry
Abstract: We report on the molecular and morphological characterization of a novel type B trichothecene toxin-producing species (i.e. B clade) recovered from litter in a maize field near Wellington, New Zealand, which is described as Fusarium praegraminearum sp. nov. This species was initially identified as F. acuminatum based on morphological characters. However, it differs from this species by producing longer, slightly asymmetrically curved macroconidia in which the apical cell is not as pointed and by its much faster colony growth rate on agar. Molecular phylogenetic analyses of portions of 13 genes resolved F. praegraminearum as the most basal species within the B clade. Mycotoxin analyses demonstrated that it was able to produce 4-acetylnivalenol and 4, 15-diacetylnivalenol trichothecenes, the nontrichothecene sesquiterpenes culmorin and hydroxy-culmorins, and the estrogen zearalenone in vitro. Results of a pathogenicity experiment revealed that F. praegraminearum induced moderate head blight on wheat.